Hydraulic properties of compacted residual soils using disk infiltrometer test - Sim, Peck Cheng. (2009)
Most soil mechanics theories were derived using the basis of saturated soils, however, civil engineers often encountered unsaturated soils. Therefore it is important to determine unsaturated properties, such as the permeability of unsaturated soil. For this project, a disk infiltrometer is used to determine the permeability of compacted residual soil. Residual soils are compacted at different compaction efforts to vary the void ratio for each different sample, since permeability of soil is affected by the changes in void ratio are tested. Matric suction of the compacted sample was measured using the null-type axis translation apparatus. Disks infiltrometer tests were conducted and coefficient of permeability will then be obtained through Zhang (1997) equation, making use of van Genuchten parameters. Pressure plate test was conducted by Ng (2009) to obtain the soil water characteristic curves (SWCC). Comparison was made with the fitted van Genuchten parameters obtained from SWCC. Results showed that coefficient of permeability obtained using fitted van Genuchten parameters from SWCC experiment were more accurate as compared to using general parameters to determine the coefficient of permeability from the disk infiltrometer tests.